2011
DOI: 10.3892/mmr.2011.543
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vector-mediated siRNA knockdown of the YAP gene inhibits growth and induces apoptosis in the SGC7901 gastric cancer cell line

Abstract: Abstract. Gastric carcinoma is among the most prevalent malignancies, and a leading cause of cancer deaths worldwide. The Hippo pathway defines a novel signaling pathway regulating cell proliferation. The key factor in this kinase cascade is the transcriptional co-activator yes-associated protein (YAP), which is constitutively activated in various types of cancer, including gastric carcinoma. To determine the effect on SGC7901 gastric cancer cells after inhibition of the YAP expression, we used lentivirus-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…Based on the high levels of conservation between Drosophila Yki and Dac and their human counterparts, our work suggests that mammalian DACH proteins might also inactivate the transcriptional activity of YAP and/or TAZ (also known as WWTR1) on a subset of target genes by interacting with specific YAP or TAZ DNA-binding partners. In agreement with this possibility, DACH1 and YAP or TAZ regulate cyclin D1 expression (Wu et al, , 2007Zhou et al, 2011). Therefore, we propose that oncogenic transformation associated with increased YAP or TAZ transcriptional activity could result not only from perturbation of YAP or TAZ localization or levels (Pan, 2010), but also from inactivation of the tissue-specific DACH co-repressors.…”
Section: Dac or Dachs And Cancersupporting
confidence: 49%
“…Based on the high levels of conservation between Drosophila Yki and Dac and their human counterparts, our work suggests that mammalian DACH proteins might also inactivate the transcriptional activity of YAP and/or TAZ (also known as WWTR1) on a subset of target genes by interacting with specific YAP or TAZ DNA-binding partners. In agreement with this possibility, DACH1 and YAP or TAZ regulate cyclin D1 expression (Wu et al, , 2007Zhou et al, 2011). Therefore, we propose that oncogenic transformation associated with increased YAP or TAZ transcriptional activity could result not only from perturbation of YAP or TAZ localization or levels (Pan, 2010), but also from inactivation of the tissue-specific DACH co-repressors.…”
Section: Dac or Dachs And Cancersupporting
confidence: 49%
“…MMP-2 is thought to be a key enzyme involved in the degradation of type IV collagen, and a high level of MMP-2 in tissues is associated with tumor growth and invasion (24). It has been reported that YAP knockdown significantly increases the GO/G1 cell population and reduces expression levels of a number of genes crucial to cell proliferation and apoptosis, including Ki-67, PCNA, survivin and cyclin 01 (25). However, little has been reported on the effect ofYAP on MMP-2 expression.…”
Section: Effect Of Knockdown Of Yap On Gastric Cancer Cell Metastasismentioning
confidence: 99%
“…YAP is a key effector protein in the Hippo pathway and is negatively regulated by the Mst1/2-LATS1/2-Mob1 complex through direct phosphorylation (11). The phosphorylation of YAP (pYAP) inhibits cell proliferation; therefore, impairment of the Hippo signaling pathway has been implicated in many human cancers including gastric cancer (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%